1985
DOI: 10.1111/j.1528-1157.1985.tb05181.x
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and Psychosis: A Comparison of Societal Attitudes

Abstract: Pioneer investigators in Nigeria have presented a gloomy picture of epilepsy as a highly infectious and disastrous disease in the eyes of the public. As a result, epileptic persons suffer untold social deprivations and discrimination in education, employment, housing, marital life, etc. These assertions have been repeated over the years more as a result of incidental observations while reviewing hospital cases than as products of attitude research on the subject. We assumed, therefore, that these statements sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…We interviewed two groups of parents, those who had a child with epilepsy and those with unaffected children. Past studies had demonstrated that interviewing only patients with epilepsy could lead to biased results in the sociocultural context of Africa [22]. Sampling a more diverse population gave us a broader view of parental beliefs and attitudes regarding epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…We interviewed two groups of parents, those who had a child with epilepsy and those with unaffected children. Past studies had demonstrated that interviewing only patients with epilepsy could lead to biased results in the sociocultural context of Africa [22]. Sampling a more diverse population gave us a broader view of parental beliefs and attitudes regarding epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…29 The endorsement of pluralism in this situation may probably reflect an affirmation of misconceptions about the causes of epilepsy and has within it a negative helpseeking implication which may result in delayed presentation for care, development of complications from the disorder, and prolonged disability and unmitigated suffering. 11,30 All these have the potential of further worsening the epilepsy treatment gap and the stigma for affected persons and their families. 31 It is however, the responsibility of concerned clinicians to educate the patients, their caregivers and the general public on the appropriate first response in the treatment of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in Madagascar, patients with epilepsy are refused burial in the family grave 2 . In many African countries, the PWE is an out-cast 6 as Africans believe that the disease results from visitation of the devil, effect of witch-craft, the revenge of an aggrieved ancestral spirit or consumption of something harmful in utero 7,8 . Suicide or attempted suicide is not uncommon among Nigerians who suffer from epilepsy 9,10 .…”
Section: Introductionmentioning
confidence: 99%